VEGF receptor antagonist Cyclo-VEGI reduces inflammatory reactivity and vascular leakiness and is neuroprotective against acute excitotoxic striatal insult - Ryu, Jae K (BioMed Central, 2008)
BACKGROUND: Excitotoxic brain insult is associated with extensive neuronal damage but could also cause inflammatory reactivity and vascular remodeling. The effects of the vascular endothelial growth factor (VEGF) inhibitor, Cyclo-VEGI on expression of VEGF, microgliosis and astrogliosis, blood-brain barrier (BBB) integrity and neuronal viability have been studied following intra-striatal injection of the excitotoxin, quinolinic acid (QUIN). The purpose of this study was to examine VEGF-dependent inflammatory responses in excitotoxin-injected brain and their dependence on pharmacological antagonism of VEGF receptors. METHODS: Single and double immunofluorescence staining of cellular (microglia, astrocyte, neuron) responses and dye and protein infiltration of blood-brain barrier have been applied in the absence, and presence, of pharmacological modulation using a VEGF receptor antagonist, Cyclo-VEGI. Dunn-Bonferroni statistical analysis was used to measure for significance between animal groups. RESULTS: Detailed analysis, at a single time point of 1 d post-QUIN injection, showed excitotoxin-injected striatum to exhibit marked increases in microgliosis (ED1 marker), astrogliosis (GFAP marker) and VEGF expression, compared with PBS injection. Single and double immunostaining demonstrated significant effects of Cyclo-VEGI treatment of QUIN-injected striatum to inhibit microgliosis (by 38%), ED1/VEGF (by 42%) and VEGF striatal immunoreactivity (by 43%); astrogliosis and GFAP/VEGF were not significantly altered with Cyclo-VEGI treatment. Leakiness of BBB was indicated by infiltration of Evans blue dye and plasma protein fibrinogen into QUIN-injected striatum with barrier permeability restored by 62% (Evans blue permeability) and 49% (fibrinogen permeability) with Cyclo-VEGI application. QUIN-induced toxicity was demonstrated with loss of striatal neurons (NeuN marker) and increased neuronal damage (Fluoro-Jade marker) with significant neuroprotection conferred by Cyclo-VEGI treatment (33% increase in NeuN and 38% decrease in Fluoro-Jade). CONCLUSION: An antagonist for VEGF receptor-mediated signaling, Cyclo-VEGI, has shown efficacy in a broad spectrum of activity against striatal excitotoxic insult including inhibition of microgliosis, reduction in leakiness of BBB and parenchymal infiltration of plasma fibrinogen and in conferring significant protection for striatal neurons. Antagonism of VEGF-mediated activity, possibly targeting VEGF receptors on reactive microglia, is suggested as a neuroprotective mechanism against inflammatory reactivity and a novel strategy to attenuate acute excitotoxic damage.